A study on cisplatin -paclitaxel induced peripheral neuropathy in cancer patients - C., Umamaheshwari; M., Shanthi; M., Malathi (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Chemotherapy induced peripheral neuropathy is a significant disability after the treatment of large number of cancers and they have an impact on quality of life. The aim of the present endeavour was to study the cisplatin-paclitaxel induced peripheral neuropathy in patients with lung or ovarian cancer Methods: The study was carried out in the Department of Oncology, Government Rajaji Hospital, Madurai, after obtaining clearance from Institutional ethical committee, Government Rajaji Hospital, Madurai. Thirty newly diagnosed patients suffering from Lung or ovarian cancer attending Oncology department were selected. After satisfying inclusion and exclusion criteria. Patient received injection cisplatin 60 mg/m2 and injection paclitaxel 175 mg/m2. Nerve conduction study was done to assess the peripheral neuropathy. It was done before starting the chemotherapy. Patients with grade 0 neuropathy were included for the study. Nerve conduction study was repeated after each cycle. The time taken to develop peripheral neuropathy was assessed using Cancer Institute - Common Toxicity Criteria version 3.0. The data were analyzed with SPSS statistical software package (Version 16.0 SPSS Inc., Chicago, USA ). Results: There is a statistically significant reduction in sensory nerve (sural) amplitude (SNAP) and latency (p <0.05) indicating significant axonal damage. The time taken to develop peripheral neuropathy was 3 cycles with grade 3/4. Conclusions: In this present study, the neurotoxicity induced by cisplatin-paclitaxel in patients with lung or ovarian carcinoma was observed, so that early intervention can prevent the permanent neurotoxicity.